Research of Thermoelectric Material Ti1-xNbxNiSn - Romaka, V.A.; Stadnyk, Yu.V.; Romaka, L.P.; Horyn, A.M.; Romaka, V.V.; Haraniuk, P.I. (Journal of Thermoelectricity, 2025)
The structural, kinetic, energetic, and magnetic properties of the semiconductor thermoelectric material Ti1-xNbxNiSn, obtained by doping n-TiNiSn with Nb atoms, have been studied. It has been shown that Nb atoms (4d45s1) simultaneously occupy different crystallographic positions, generating structural defects of donor and acceptor nature. At Ti1-xNbxNiSn concentrations, х=0–0.04, Nb atoms predominantly replace Ti (3d24s2) and Ni (3d84s2) atoms present there in position 4a, generating donor and acceptor states in the band gap εg, respectively. At higher concentrations, х˃0.04, Nb atoms replace only Ti atoms, generating structural defects and energetic states of donor nature. It is shown that the semiconducting solid solution Ti1-xNbxNiSn is a promising thermoelectric material, and at T≈650 K and Ti0.99Nb0.01NiSn concentration ZT is equal to 0.76. The studies allowed us to identify the mechanisms of electrical conductivity to determine the conditions for the synthesis of thermoelectric materials Ti1-xNbxNiSn with maximum efficiency of converting thermal energy into electrical energy.